Ruptured abdominal aortic aneurysms early recognition, hemodynamic stabilization, and emergency vascular surgery - Aljefri, Ahmed Amin; Alhajji, Ahmed Abdulhadi; Al Shammari, Fahad Waed; Habib, Esra Salman Al; Alanazi, Mohammed Ghanem; Esam, Anfal Sayed; Alghamdi, Faisal Abdullah; Alajmi, Hassan H.; Basahal, Nojoud Mohammed; Qattan, Khadijah Mohammed; Alwakeel, Abdullah Abdulrahman (International Journal Of Community Medicine And Public Health, 2023)
Ruptured abdominal aortic aneurysms (rAAAs) are extremely dangerous. Require attention. This thorough review explores the management of rAAA, focusing on the detection stabilizing blood flow and emergency vascular surgery. Recognizing symptoms such as intense abdominal pain, low blood pressure, a pulsating mass in the abdomen, signs of reduced blood flow to the lower limbs, and back pain is crucial for quick identification. Diagnostic imaging techniques like ultrasound and computed tomography angiography (CTA) play a role in confirming the diagnosis and assessing the risk involved. Properly managing hemodynamics by balancing resuscitation efforts with approaches is essential to control ongoing bleeding. Emergency vascular surgery options include aneurysm repair (EVAR) and open repair; the choice depends on factors like anatomy, stability of blood flow, and surgical expertise. Prioritizing optimization to address any health conditions and closely monitoring patients after surgery greatly contribute to overall success rates. A collaborative approach among healthcare professionals ensures a multidisciplinary strategy during the period emphasizing effective communication. This comprehensive approach aims for outcomes in dealing with challenging rAAAs while considering advancements in research and clinical practices.